Vertically ordered mesoporous silica film-assisted electrochemical cytosensor for the sensitive detection of HeLa cells - Zeng, Zisan; Zhao, Yang; Yang, Luoxing; Xi, Fengna; Su, Danke (Frontiers in Chemistry, 2023)
Designing fast and simple quantitative methods on cheap and disposable electrode for early detection of Hela cells is highly desirable for clinical diagnostics and public health. In this work, we develop a label-free and sensitive electrochemical cytosensor for Hela cells detection based on the gated molecular transport across vertically-ordered mesoporous silica films (VMSF) on disposable indium tin oxide (ITO) electrode. As high affinity for folate receptor existed on the membrane of Hela cancer cells, folic acid (FA) functionalized VMSF could regulate the transport of electrochemical probe (Fe(CN)6 3-) by the specific recognition and adhesion of Hela cells to the VMSF surface. In addition, VMSF served as a solid skeleton is able to effectively pre-vent the direct contact of cell with the underlying electrode, remaining the underlying electrode activity and favoring the diffusion of Fe(CN)6 3-. Once specific adhesion of Hela cells to the VMSF surface, Fe(CN)6 3-redox probe exhibits impeded transport in the silica nanochannels, ultimately resulting in the decreased electrochemical responses and realizing the quantitative determination of Hela cells with a broad linear range (10 1 to 10 5 cells/mL) and a low limit of detection (4 cells/mL). The proposed electrochemical cytosensor shows great potential application for early diagnosis of cervical cancer.